Introduction of Blue Energy in the Mediterranean: The Conceptualization of the Sea as “Space” and Emerging Opportunities for Greece and Mediterranean Countries - Fotiadou, Angeliki; Papagiannopoulos-Miaoulis, Ilias (Frontiers in Energy Research, 2019)
When we think of the term “space”, we tend to imagine an onshore area with certain features, such as borders, governing laws and regulations, land uses, geomorphology, materials and substance. Seldom, however, we will think of the sea as “space”, despite the fact that it has all the aforementioned characteristics: it covers a certain area, it has specific features and serves different operations. For Mediterranean countries like Greece, the sea has always been a core element of their identity in both geographical and cultural terms. Throughout history, the sea served as a means to boost their economies through trade and other maritime activities and their culture through interaction with other cultures and civilizations. Nowadays, the sea is set to play yet another important role in terms of renewable energy exploitation and energy self-sufficiency. One can therefore easily understand how important this “space” is. However, the sea’s significance in these aspects has not been fully fathomed yet, nor is it considered as a “space” that needs to follow specific rules for its “healthy” development. This paper tries to identify how the introduction of Blue Energy can function as a driving force for the conceptualization of the Mediterranean Sea as “space” and, subsequently, for its regulation. Furthermore, it is presenting the opportunities that Blue Energy technologies can bring to Greece and to any Mediterranean country for a prosperous, environmentally friendly and sustainable future.